2005
DOI: 10.1270/jsbbs.55.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of QTLs for Early Elongation Ability between Two Floating Rice Cultivars with a Different Phylogenetic Origin

Abstract: The ability to initiate stem elongation at the early growth stages of a plant is the major survival mechanism of floating rice in the presence of flooding. We previously identified two quantitative trait loci (QTLs) for this "early elongation ability" on chromosomes 3 and 12 using a Patnai23 (a non-floating cultivar) × Goai (a floating cultivar) F 2 population. The objectives of the present study were: (1) to identify QTLs for early elongation ability in the cross Habiganj Aman VIII (a floating cultivar) × Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…They identified QTLs for LEI on chromosomes 3 and 12, which were located at almost the same positions as in our results. On the same region of chromosome 12, they also detected QTL affecting LEI from different deepwater variety 'Habiganj AmanVIII' (Tang et al 2005). These QTLs for LEI are probably widely distributed among deepwater rice varieties.…”
Section: Discussionmentioning
confidence: 91%
“…They identified QTLs for LEI on chromosomes 3 and 12, which were located at almost the same positions as in our results. On the same region of chromosome 12, they also detected QTL affecting LEI from different deepwater variety 'Habiganj AmanVIII' (Tang et al 2005). These QTLs for LEI are probably widely distributed among deepwater rice varieties.…”
Section: Discussionmentioning
confidence: 91%
“…To evaluate deepwater rice traits, it is important to measure the TIL, NEI and LEI (Vergara & Mazaredo 1979;Inouye & Mogami 1980;Nemoto et al 2004;Tang et al 2005;Hattori et al 2007;Kawano et al 2008). However, these measurements do not quantify each internode elongation.…”
Section: Gross Morphology and Internode Elongation Patterns In Deepwamentioning
confidence: 99%
“…In this report, we determined whether specific internodes in deepwater rice elongate under DW conditions. Previous studies revealed that three major QTLs regulate DW responses (Nemoto et al 2004;Tang et al 2005;Hattori et al 2007;Kawano et al 2008). In this study, we used a QTL pyramiding line (NIL-1 + 3 + 12) carrying C9285 (deepwater rice) genomic fragments possessing three major QTLs on chromosomes 1, 3 and 12 in the T65 (general cultivated rice) genetic background to examine internode elongation patterns and initiation under DW conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Three quantitative trait loci (QTLs) located on chromosomes 1, 3, and 12 controlled internode elongation in deep‐water rice (Tang et al, 2005). Two subsequent studies that used different mapping populations verified the effect and locations of these three QTLs (Hattori et al, 2007; Kawano et al, 2008).…”
mentioning
confidence: 99%